Discourse Deixis and its Pecularities in the English Language - Sharipova Fazilat (International Journal on Integrated Education, 2022)
The discourse deixis is found to be used in the English language to express the interpersonal relationships involved between the speaker and listener in conversation. The article explores some peculiarities of discourse deixis in the English language. It is noted in the article that while the traditional categories of the deixis are the most obvious examples, there are other types of deixis that are widely available. These categories are for the first time discussed by Fillmore and Lyons. These categories are categories of social deixis and discourse deixis. Our article deals with the use of the discourse deixis in English. The article also covers discussion of linguistic views of scientists in this field. We think that urgency of the work just lies in the theoretical problems discussed in the article. The article is also of both theoretical and practical importance in the view of learning English and developing the science of linguistics as a whole.